2022
DOI: 10.1039/d2tb00679k
|View full text |Cite
|
Sign up to set email alerts
|

From main-chain conjugated polymer photosensitizer to hyperbranched polymer photosensitizer: expansion of the polymerization-enhanced photosensitization effect for photodynamic therapy

Abstract: Three conjugated polymers with the same donor-acceptor structure but totally different architectures are design to show both Type-I and Type-II photosensitization abilities simultaneously, among which the hyperbranched polymer shows the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…To further investigate the ROS production processes, hydroxyphenyl fluorescein (HPF) and 1 O 2 sensor green (SOSG) were used to measure the types of ROS, which suggested the generation of both • OH and 1 O 2 (Figures S10 and S11). , These revealed that MDNPs were able to function as efficient PDT agents with both type I and type II processes thanks to the efficient ISC process.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…To further investigate the ROS production processes, hydroxyphenyl fluorescein (HPF) and 1 O 2 sensor green (SOSG) were used to measure the types of ROS, which suggested the generation of both • OH and 1 O 2 (Figures S10 and S11). , These revealed that MDNPs were able to function as efficient PDT agents with both type I and type II processes thanks to the efficient ISC process.…”
Section: Resultsmentioning
confidence: 94%
“…2′,7′-Dichlor- S11). 58,59 These revealed that MDNPs were able to function as efficient PDT agents with both type I and type II processes thanks to the efficient ISC process.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, to further expand the polymerization-enhanced photosensitization effect, our group prepared three different types of AIE CPs: the main chain type, P13, side chain type, P14, and hyperbranched type, P15, with the same donor and acceptor (Figure 7D). [55] Owing to the reversible redox capacity of the AQ moiety, all three polymers produced not only 1 O 2 but also superoxide radicals (O 2…”
Section: Polymerization-enhanced Photosensitization Effectmentioning
confidence: 99%
“…Recently, to further expand the polymerization‐enhanced photosensitization effect, our group prepared three different types of AIE CPs: the main chain type, P13 , side chain type, P14 , and hyperbranched type, P15 , with the same donor and acceptor (Figure 7D). [ 55 ] Owing to the reversible redox capacity of the AQ moiety, all three polymers produced not only 1 O 2 but also superoxide radicals (O 2 •− ) and hydroxyl radicals (•OH) by Type‐I photosensitization upon excitation. In comparison with the traditional main‐chain and side‐chain CPs, the special 3D dendritic structures of P15 could improve the contact with oxygen, leading to higher ROS‐generation efficiencies.…”
Section: Polymerization‐enhanced Photosensitization Effectmentioning
confidence: 99%
“…Third, polymers as active bio‐targeting groups. Materials with pronounced triplet activity after photoexcitation are routinely assessed as antimicrobial agents for photodynamic therapy [4, 44–48] . For pathogenic bacterial, for example, the more localized negative charge can make them a target for positively charged polymers (e.g., commercially used polyhexamethylene guanidine).…”
Section: Introductionmentioning
confidence: 99%